PENGEMBANGAN MODUL APLIKASI KOMPUTER DALAM MENDESAIN RAGAM HIAS MENGGUNAKAN PROGRAM CORELDRAW X4 UNTUK MAHASISWA JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Afrianti, Dewi; Ernawati, Ernawati; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
Computer applications courses mandatory for students dressmaking Family Welfare Department, but there is no module as media student learning, so that students are less active and creative in the PBM. This study aims to generate media forms of learning modules that can help students dressmaking Department of Family Welfare in learning computer applications to design decorative materials using CorelDRAWX4 program. Research also gain an overview of the feasibility of the learning module as a learning medium of computer applications, including the validation module and the practicalities of the module.This study is a Research and Development (R & D) is a research method used to produce a particular product and test the feasibility of the product. In this case a learning module. This learning module is tested its validity by 4 people validator experts in media and materials and tests performed on the practicalities of S1 students dressmaking class of 2014 the number of 18 people. The steps undertaken in the development of this learning module are: 1) define phase. 2) design phase, 3) stages develop. At this stage of the development of data analysis, namely: 1) the validity of the data analysis module, 2) data analysis module practicalities. Data analysis techniques used by calculating the mean.Based on the research results, test the validity of the obtained scores of 4.31 validator can be categorized as very valid. While the practicalities of the test results performed to a small group of students obtained a score of 3.21 categorized as very practical while testing the practicalities of a large group obtained a score of 3.54 categorized as very practical. These modules are in decent Criteria used as a medium of learning courses computer applications student dressmaking Family Welfare Department, Faculty of Engineering University of Padang on designing decorative materials using CorelDRAW X4 program.Kata kunci: Pengembangan Modul , aplikasi komputer, mendesain ragam hias menggunakan progrgram CorelDRAW X4